Culture as a factor in the professional practice of interior design - Peña, Micaela Ethylene G.
This qualitative research aimed to determine how culture plays a role in the professional practice of interior design. Fourteen (14) licensed Filipino interior designers who had at least five (5) years of work experience were interviewed for the study. The informants were selected through purposive sampling and all were based in Metro Manila. An interview questionnaire, a pen and notebook and a voice recorder were used to gather data. The study employed coding methods to analyze the interview data. Results revealed that culture was a factor in the professional practice of interior design as indicated in the work performance, working/professional relationship, and social relationships of people involved in the profession. Certain values and attitudes such as Filipino time, mañana habit (procrastination) and being madamdamin (emotional) hindered the quality and productivity of work performance. On the other hand, pakikisama (getting along), personalism, and familism had a positive influence on professional and social relationships; however this did not ensure efficiency in the work performance of Filipinos in the industry. Cultural values such as being masipag (hardworking) and magaling (skilled) can also affect work performance in a good way if they are observed in the workplace. Filipino interior designers must be aware of their cultural values, attitudes and habits and use them effectively in a way that does not affect the practice of interior design negatively.